(3GdMOGFb GdhQOjI aj efGbH GdCFeI GdRHOjIs - (3MejO Hf CMeO GdnenMpqdj GdgeOGfqj, CHh YHO Gddg MSGe GdOjf, GdeYQha HGdbGVj GdTgjO,J (B652 (3g` s
(3ChdgG (B:s
(3JQLeI GdEeGe GdbGSe GdYUQ GHf GHQGgje Hf ESeGYjd s
(3jdi gPG GdLRA dhGMb GdMOGFb GdhQOjI HJQGLe CYGXe GdCFeI GdOYGI ef GdYJQI GdfHhjIs
(3hgPG GdLRA ai eLdO HGdJUhjQ GdTeSj fbdkG Yf fSNI eNWhWI eMahXI HUfYGAs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B282 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B83s
Keywords: (3GdJGQjNs